ISAT903, An Assessment Tool on the Quality System for Software Industry - Mohd Kasirun, Zarinah; Amirudin, Burhani (Malaysian Journal of Computer Science, 2000)
Software industry is currently facing numerous problems. As such, continuing emphasis has been given in finding ways to solve the problems with main focus on improving software development quality and productivity. Quality and productivity are weapons that have to be utilized by any enterprising organizations to win dominance in the global market as well as in the competitive market of the information age. One of the solutions to these problems is an implementation of software engineering tools and techniques, such as Computer Aided Software Engineering (CASE) Technology and CASE tools. But up-to-date with the tools only, the software industry is unable to solve these problems completely. This paper presents and proposes a compliance model on the quality system for software development by ISO 9000-3 as a conceptual combination of the Total Quality Management, Software Engineering concept and application of the quality system standard ISO 9000-3.